PRECEDENT PHENOMENA IN THE MEDIA: A TOOL FOR SHAPING PUBLIC OPINION IN THE REPUBLIC OF UZBEKISTAN AND THE RUSSIAN FEDERATION (Web of Teachers: Inderscience Research, 2025)
This article examines the role of precedent phenomena in shaping public opinion through the media in Russia and Uzbekistan.